Answer:
8x^3-7x^2-11x+9
Step-by-step explanation:
(8x^3-5x-1)-(7x^2+6x-10)
remove unnesasary ( )
8x^3-5x-1 -(7x^2+6x-10)
the distribute
8x^3-5x-1 -7x^2-6x+10
combine like terms
8x^3-11x+9-7x^2
use the communative property to reorder the equation
8x^3-7x^2-11x+9
Answer:
nuber 1
Simplifying
3x + 2y = 35
Solving
3x + 2y = 35
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-2y' to each side of the equation.
3x + 2y + -2y = 35 + -2y
Combine like terms: 2y + -2y = 0
3x + 0 = 35 + -2y
3x = 35 + -2y
Divide each side by '3'.
x = 11.66666667 + -0.6666666667y
Simplifying
x = 11.66666667 + -0.6666666667y
A= 108 centimeters sqaured if you are on oddeseyware thats the correct answer
Answer:
x= √2 - 2 + √5-4√2, √2-2 - √5-4 √2
Answer:
gsjdudvegdiddbdb
Step-by-step explanation:
njshsuebsbhssnshssje